Prevalence and description of kratom (Mitragyna speciosa) use in the United States: a cross‐sectional study. (28th April 2020) - Schimmel, Jonathan; Amioka, Elise; Rockhill, Karilynn; Haynes, Colleen M.; Black, Joshua C.; Dart, Richard C.; Iwanicki, Janetta L.
Abstract: Background and aims: Mitragyna speciosa ('kratom') contains mu opioid partial agonists. It is widely available, and occasionally used as a home remedy for opioid use disorder. The Drug Enforcement Agency considers kratom a drug of concern; however, prevalence of use and role in drug misuse are unknown. This study aimed to characterize kratom use in the United States. Design: Cross‐sectional Survey of Non‐Medical Use of Prescription Drugs (NMURx) Program, 2018 third quarter and 2019 first quarter. Setting: A validated non‐probability online survey in the United States. Participants: A total of 59 714 respondents aged 18 years or older, weighted to represent the adult US population ( n  = 252 063 800). Measurements: In addition to prevalence of past‐year kratom and other drug use, behavior proportions were estimated. The Drug Abuse Screening Test (DAST‐10) estimated consequences of drug abuse. Findings: The estimated prevalence of past‐year kratom use in the adult US population was 0.8% [95% confidence interval (CI) = 0.7–0.9], representing 2 031 803 adults. Life‐time prevalence was 1.3% (95% CI = 1.2–1.4), representing 3 353 624 adults. Kratom users were younger (mean 35 years, P  < 0.001), with higher proportions of males (61.0 versus 48.6%, P  < 0.001), students (14.1 versus 7.5%, P  < 0.001) and health‐care professionals (9.7 versus 4.5%, P  < 0.001) and fewer bachelor's/advanced degree graduates (33.4 versus 42.6%, P  < 0.001) compared with non‐users. Results were inconclusive on whether there was a difference in kratom use by race, household income or employment status. Among those with past‐year kratom use, 36.7% (95% CI = 32.1–41.3) non‐medically used prescription opioids, 21.7% (95% CI = 18.0–25.5) used illicit opioids, 54.4% (95% CI = 49.5–59.3) used another illicit drug and 67.1% (95% CI = 62.5–71.8) used cannabis. The DAST‐10 profile was more often substantial/severe in kratom users (21 versus 1%, P  < 0.001) compared with non‐users. Conclusions: Estimated United States past‐year prevalence of kratom use is 0.8%, and kratom users tend to have more serious substance abuse profiles than non‐users or users of cannabis, alcohol or cigarettes. To our knowledge, this is the first description of kratom use at the national level.